2012
DOI: 10.4161/auto.21211
|View full text |Cite
|
Sign up to set email alerts
|

ROS-induced mitochondrial depolarization initiates PARK2/PARKIN-dependent mitochondrial degradation by autophagy

Abstract: Reactive oxygen species (ROS) have been implicated as a signal for general autophagy. Both mitochondrial-produced and exogenous ROS induce autophagosome formation. However, it is unclear whether ROS are required for the selective autophagic degradation of mitochondria, a process called mitophagy. Recent work using carbonyl cyanide m-chlorophenylhydrazone (CCCP), a mitochondrial-uncoupling reagent, has been shown to induce mitophagy. However, CCCP treatment may not be biologically relevant since it causes the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
292
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 380 publications
(317 citation statements)
references
References 30 publications
(56 reference statements)
20
292
2
3
Order By: Relevance
“…A recent report showed that ROS generated from a defined set of mitochondria are sufficient to cause depolarization, and that these mitochondria are subsequently degraded by mitophagy. 23 This report further highlights the close link between mitochondrial ROS generation, mitochondrial membrane potential, and mitophagy. Further work will help to clarify the exact role of mitochondrial membrane potential as a marker and/or signal for the induction of mitophagy.…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…A recent report showed that ROS generated from a defined set of mitochondria are sufficient to cause depolarization, and that these mitochondria are subsequently degraded by mitophagy. 23 This report further highlights the close link between mitochondrial ROS generation, mitochondrial membrane potential, and mitophagy. Further work will help to clarify the exact role of mitochondrial membrane potential as a marker and/or signal for the induction of mitophagy.…”
Section: Introductionsupporting
confidence: 53%
“…The second family are the GABA A receptor-associated proteins (GABARAP) which has four members: the first is GABARAP, the second member is GABARAPL1 (GABA(A) receptor-associated protein like 1)/ATG8L/GEC1, the third member is GABARAPL2 (GABA(A) receptor-associated protein like 2)/GATE-16/GEF2, with the final member GABARAPL3 (GABA(A) receptor-associated protein like 3). 28 Examples where mitochondria have been labeled along with MAP1LC3 as either a fluorescent protein (FP) chimera 19,21,23,29 or by using antibodies raised against MAP1LC3 30 are noted. MAP1LC3 reporters can also be combined with many other mitochondrial/mitophagy fluorescent markers, including TMRM, 21 mitochondrial-targeted RFP, 19 PARK2 as an FP chimera, 30,31 PINK1 (Flag epitope-tagged PINK1), 30 and MitoTracker ® dyes.…”
Section: Monitoring Mitophagy Through Colocalization Of Mitochondrialmentioning
confidence: 99%
See 3 more Smart Citations